Preparation method of low-magnetism oil-soluble aniline black
By adding oxidation treatment steps in the preparation process of oil-soluble aniline black, the oxidized divalent ion is trivalent ion, which solves the problem of high magnetic susceptibility of oil-soluble aniline black products in the prior art, and reduces the magnetic susceptibility and improves the magnetic susceptibility The goal of product usage effect.
Patent Information
- Application Number
- CN202411408085.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-02-18
AI Technical Summary
In the prior art, the oil-soluble aniline black products have a high magnetic susceptibility, resulting in equipment damage and poor use effect.
In the process of preparing the oil-soluble aniline black product, an oxidation treatment step is added to oxidize the divalent iron ions present in the material into trivalent iron ions, thereby reducing the magnetic susceptibility of the final product.
By adding the oxidation treatment step, the magnetic susceptibility of aniline black products is effectively reduced, reducing it to below 5%, significantly improving the product's use effect and avoiding equipment damage.
Smart Images

Figure CN119462534A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of dye manufacturing, and in particular relates to a method for preparing low-magnetic oil-soluble aniline black. Background Art
[0002] In the prior art, such as Figure 1 As shown, the production process of oil-soluble aniline black is basically based on aniline and nitrobenzene as the main raw materials. In the presence of ferric chloride, after preheating and condensation reaction, it enters the acidification process for acidification, and then after water washing and solid-liquid separation, the solid filter cake enters the saponification process for saponification reaction with liquid alkali, and then is washed, dried and packaged into products.
[0003] Specifically, in the above production process, the reaction formula of the condensation reaction is as follows:
[0004]
[0005] During the condensation reaction, the trivalent iron ions in the ferric chloride are converted into divalent iron ions, so that the oil-soluble aniline black product finally obtained has a high magnetizability due to the large amount of divalent iron. In the process of making masterbatch from the oil-soluble aniline black obtained by the above production process, there is a problem of equipment damage due to the high magnetic susceptibility. At the same time, the high magnetizability of the oil-soluble aniline black product is also easy to affect its use effect during use.
[0006] In view of this, the present invention is proposed. Summary of the invention
[0007] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art and provide a method for preparing low-magnetic oil-soluble aniline black, which can effectively reduce the magnetizable rate of the aniline black product.
[0008] In order to solve the above technical problems, the basic concept of the technical solution adopted by the present invention is:
[0009] A method for preparing low-magnetic oil-soluble aniline black comprises the following steps:
[0010] (1) mixing aniline raw material and ferric chloride, heating up and preheating;
[0011] (2) adding nitrobenzene to the preheated material to carry out a condensation reaction to obtain a condensate;
[0012] (3) acidifying and washing the condensate in sequence;
[0013] (4) mixing the washed material with a nitric acid solution and performing an oxidation treatment;
[0014] (5) mixing the oxidized material with liquid alkali and performing saponification treatment;
[0015] (6) The saponified material is washed with water and dried in turn to obtain a nigrosine product.
[0016] In the above scheme, the oxidation treatment of the material is added before the saponification process in the preparation process, so that the divalent iron ions (Fe 2+ ) is oxidized to ferric ion (Fe 3+ ), thereby effectively reducing the Fe content in the final aniline black product 2+ content, avoid Fe 2+ The presence of aniline black causes the problem of high magnetizable rate of aniline black products. By adding the step of oxidation treatment, the magnetizable rate of aniline black products can be simply and effectively reduced, avoiding affecting the use effect of aniline black products.
[0017] An oxidation treatment step is added between the water washing step after the acidification treatment and the subsequent saponification step. On the one hand, a certain amount of Fe can be washed away by the water washing step. 2+ , avoiding the problem of consuming a large amount of nitric acid for oxidation. On the other hand, liquid alkali will be added to the material during the subsequent saponification treatment, which can neutralize the added nitric acid and ensure that the pH value index of the obtained aniline black product is within the qualified range. If nitric acid is added for oxidation after the saponification treatment, it may cause the aniline black product to be acidic. At the same time, after the acidification and water washing steps, the material contains only a small amount of aniline hydrochloride, ferric chloride and ferrous chloride in addition to the intermediate product of aniline black in the preparation process. During the oxidation process, in addition to Fe 2+ ) is oxidized to Fe 3+ In addition to the reaction, there are basically no other side reactions, and thus there is no problem of introducing impurities into the final aniline black product during the oxidation treatment step.
[0018] Furthermore, in step (4), after the washed material is mixed with the nitric acid solution, the mixture is heated to 70-100° C. and kept warm for 2-4 hours;
[0019] Preferably, the mixture is heated to 80-90° C. and kept warm for 2-4 hours;
[0020] More preferably, the mixture is heated to 80°C and maintained at that temperature for 4 hours.
[0021] In the above scheme, the temperature and holding time of the oxidation treatment process are controlled within the above range, and the obtained aniline black product is tested, and the magnetizable rate can be reduced to less than 5%, which significantly improves the qualified rate of the aniline black product in the magnetizable test. Among them, the magnetizable rate refers to the proportion of magnetic particles after the aniline black product is made into particles of uniform size. Correspondingly, the proportion of non-magnetic particles is the qualified rate of magnetizable iron of the aniline black product. It can be understood that the magnetizable rate + the qualified rate of magnetizable iron = 100%.
[0022] Furthermore, in step (3), a filter is used to wash the acidified material, and the washed material is a filter cake;
[0023] In step (4), the mass of nitric acid in the nitric acid solution is 1.0% to 3.0% of the mass of the filter cake in step (3), preferably 1.5% to 2.3%;
[0024] Preferably, in step (3), the acid content in the material after water washing is less than or equal to 0.5%.
[0025] In the above scheme, the solid content of the filter cake is about 50wt%, wherein Fe 2+ The mass proportion in the solid matter is about 1wt%, based on 3 mol Fe 2+ 4 mol HNO3 is required for oxidation calculation, and the theoretical amount of nitric acid is about 0.76% of the filter cake mass. The actual amount of nitric acid added is controlled at 1.0% to 3.0% of the filter cake mass, which is greater than the theoretical amount of nitric acid, which is beneficial to ensure that the Fe contained in the filter cake 2+ Fully oxidized to Fe 3+ , to minimize Fe 2+ At the same time, the amount of nitric acid added should not be too large, so as to avoid making the material too acidic, causing the final aniline black product to fail the test in terms of pH value.
[0026] Furthermore, in step (4), a nitric acid solution with a mass concentration of 65% to 68% is added to water for dilution, and then the filter cake obtained in step (3) is added to the diluted nitric acid solution and heated for oxidation treatment;
[0027] Preferably, the mass of water used to dilute the nitric acid solution is 1 to 3 times the mass of the filter cake, preferably 1.5 times.
[0028] In the prior art, the filter cake obtained after acidification and water washing needs to be pulped to form a slurry before being subjected to saponification. In the above scheme, the filter cake is added to a diluted nitric acid solution for oxidation reaction, and while the oxidation process is being realized, the pulping operation of the filter cake is also completed. After the oxidation is completed, the subsequent saponification treatment step can be directly carried out, saving the preparation process.
[0029] Furthermore, in step (5), liquid alkali and hot water at a temperature of 90 to 95° C. are added to the saponification kettle, and then the oxidized material obtained in step (4) is added to the saponification kettle, and then liquid alkali is continued to be added to adjust the pH to 10 to 12, and then the temperature is raised to 95 to 98° C. and kept warm for 4 to 6 hours to complete the saponification treatment.
[0030] Furthermore, in step (1), the aniline raw material comprises aniline and recovered aniline; wherein the recovered aniline comprises aniline with a mass fraction greater than 95%, and the rest is water;
[0031] Preferably, the mass ratio of the aniline to the recovered aniline is 1:0.6-0.65.
[0032] In the above scheme, after the material is washed with water in step (3), a certain amount of aniline exists in the obtained washing wastewater, and the recovered aniline is obtained by recovering and concentrating the washing wastewater through an aniline recovery system, and mainly consists of aniline and water, wherein the mass fraction of aniline is greater than 95%. When preparing the nigrosine product, the aniline raw material used includes a certain amount of recovered aniline, so that the aniline lost in the washing process is recycled and utilized, and at the same time, it is beneficial to reduce the feed amount of pure aniline, and can be used in industrial production to achieve the purpose of saving production costs.
[0033] Furthermore, in step (1), aniline and recovered aniline are added to a preheating kettle, and ferric chloride is added to the preheating kettle under stirring conditions. After the addition of ferric chloride is completed, the preheating kettle is sealed, and the temperature is raised to above 100 to 130° C. and then stopped, and the preheated materials are transported to a condensation kettle;
[0034] Preferably, ferric chloride is added into the preheating kettle at a rate of 10-15 g / min.
[0035] Furthermore, step (2) specifically includes:
[0036] The preheated material is transported to the condensation kettle and heated to 170-175°C;
[0037] Add nitrobenzene to the condensation kettle. During the addition of nitrobenzene, control the temperature of the material in the condensation kettle to be 170-185°C;
[0038] After the addition of nitrobenzene is completed, the temperature is kept at 1 to 2 hours, and then the temperature is raised to 190 to 200°C to obtain a condensate;
[0039] Preferably, nitrobenzene is added to the condensation reactor at a rate of 1.4 to 1.6 ml / min;
[0040] Preferably, the molar ratio of aniline, nitrobenzene and ferric chloride in the aniline raw material is 2.1-3.0:1:0.23-0.28;
[0041] More preferably, the molar ratio of aniline, nitrobenzene and ferric chloride is 2.37:1:0.23.
[0042] Furthermore, in step (3), hydrochloric acid and water are added to an acidification kettle and heated to 70-80° C., and then the condensate obtained in step (2) is transferred to the acidification kettle under stirring conditions for acidification treatment.
[0043] Furthermore, in step (6), a flash dryer is used to dry the washed material, and the flash outlet temperature is controlled to be 64-66° C.; the water content of the aniline black product obtained after drying is 1.0%-3.0%.
[0044] Specifically, the present invention adopts the following preparation method to prepare low magnetic oil-soluble aniline black:
[0045] (1) adding aniline and recovered aniline into a preheating kettle, and under stirring, adding ferric chloride into the preheating kettle at a feeding rate of 10 to 15 g / min. After the addition of ferric chloride is completed, sealing the feed port of the preheating kettle, adjusting the steam valve for heating, and stopping heating after the temperature rises to above 100 to 130° C., and conveying the preheated materials into a condensation kettle;
[0046] (2) After the material transportation is completed, the condensation kettle is heated to 170-175° C. by a thermal oil furnace, the temperature-raising valve of the thermal oil furnace is closed, and nitrobenzene is added to the condensation kettle by a flow meter at a feeding rate of 1.4-1.6 ml / min. During the nitrobenzene addition process, the temperature of the material in the condensation kettle is controlled to be 170-185° C.; after the nitrobenzene is added, the temperature is kept for 1-2 hours, and then the temperature is raised to 190-200° C. to obtain a condensate; wherein the molar ratio of aniline, nitrobenzene and ferric chloride is 2.1-3.0:1:0.23-0.28;
[0047] (3) adding hydrochloric acid and hot water to the acidification kettle, turning on the steam heating to 70-80° C., and transferring the condensate obtained in step (2) to the acidification kettle under stirring while maintaining the temperature at 70-80° C.; pumping the acidified material to the filter for water washing until the acid content of the obtained washing wastewater is less than or equal to 0.5%, thereby obtaining a filter cake;
[0048] (4) taking 1 to 3 times the mass of the filter cake, adding a nitric acid solution with a mass concentration of 65% to 68% to dilute it, wherein the mass of the nitric acid is 1.0% to 3.0% of the mass of the filter cake, adding the filter cake to the diluted nitric acid solution to slurry, heating to 70 to 100° C., and keeping the temperature for 2 to 4 hours;
[0049] (5) adding liquid caustic soda and hot water at a temperature of 90 to 95° C. into a saponification kettle, then adding the slurry material after oxidation treatment obtained in step (4), and then continuing to add liquid caustic soda to adjust the pH to 10 to 12, then raising the temperature to 95 to 98° C. and keeping the temperature for 4 to 6 hours;
[0050] (6) The material in the saponification kettle is conveyed to the filter for water washing, and the washed material is conveyed to the flash drying unit by a screw conveyor; the wet material enters the feed tank in the flash drying unit for storage, and is conveyed to the flash main unit by a screw conveyor in the feed tank for drying, and the flash outlet temperature is controlled to be 64-66° C., and the water content of the obtained aniline black product is 1.0%-3.0%;
[0051] (7) The aniline black product obtained after drying enters the packaging silo for packaging.
[0052] The saponified material is washed with water and dried in sequence to obtain the aniline black product.
[0053] After adopting the above technical scheme, the present invention has the following beneficial effects compared with the prior art.
[0054] In the present invention, after the acidification and water washing steps, the material is oxidized by nitric acid to remove Fe 2+ Oxidized to Fe 3+ , so that the Fe content of the final aniline black product 2+ The content is greatly reduced, thus avoiding the aniline black product due to Fe 2+ The presence of a large amount of ions causes the problem of high magnetic susceptibility.
[0055] The magnetizable rate of the aniline black product prepared by the preparation method of the present invention can be reduced to below 5%. Since the low-magnetic aniline black product is prepared, a series of problems caused by the high magnetizable rate during the use of the aniline black product can be avoided.
[0056] The specific implementation modes of the present invention are further described in detail below in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0057] The accompanying drawings are part of the present invention and are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention, but do not constitute an improper limitation of the present invention. Obviously, the drawings described below are only some embodiments. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work. In the accompanying drawings:
[0058] Figure 1 It is a production process flow chart of oil-soluble aniline black in the prior art;
[0059] Figure 2 The present invention is a flow chart of the preparation method of low magnetic oil-soluble aniline black.
[0060] It should be noted that these drawings and textual descriptions are not intended to limit the conceptual scope of the present invention in any way, but are intended to illustrate the concept of the present invention for those skilled in the art by referring to specific embodiments. DETAILED DESCRIPTION
[0061] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. The following embodiments are used to illustrate the present invention but are not used to limit the scope of the present invention.
[0062] like Figure 2 As shown, the specific embodiment of the present invention provides a method for preparing low magnetic oil-soluble aniline black, using aniline, nitrobenzene and ferric chloride as raw materials, and sequentially performing preheating, condensation, acidification, water washing, oxidation, saponification, water washing, drying and packaging steps to reduce the Fe content in the obtained aniline black product to 0. 2+ The content is greatly reduced, so that the aniline black product contains almost no Fe 2+ . Due to Fe 2+ With the decrease of content, the magnetizable rate of aniline black products is significantly reduced, thus avoiding the problem that the high magnetizable rate affects the use effect and even damages the equipment in the process of making masterbatch.
[0063] Specifically, in the embodiment of the present invention, after the aniline black product is obtained, the qualified rate of magnetizable iron and the magnetizable rate are detected by the following method:
[0064] A. Weigh 10g (accurate to 0.03g) of the prepared aniline black product and EBS dispersant, place them in a beaker, and stir them evenly with a glass rod;
[0065] B. Place the beaker on the asbestos net of the electric furnace, and slowly adjust the temperature of the electric furnace from low to high. During this period, stir the material with a glass rod to make the material evenly heated. The material gradually becomes dry and hard and then melts into a liquid state;
[0066] C. When the material is completely melted, stop heating for a while, use a glass rod to dip a small amount of molten slurry and drop it on the surface of the plate. After the slurry cools, it forms shiny semicircular black particles with a diameter of about 2mm; repeat the process of dipping and dropping particles to obtain several semicircular black particles. If the material temperature drops and becomes sticky during this period, it can be heated again;
[0067] D. After the particles are completely cooled, scrape them off with a scraper and collect them. Select 100 particles with regular shape and uniform size for the next test;
[0068] E. Place the 100 collected particles with the arc surface facing downward on the surface of a hard plate, and use a magnetic bar to move back and forth under the plate. Be careful not to vibrate the plate, and observe whether the particles on the surface will be magnetized and move with the magnetic bar. If they move, it will be recorded as unqualified. Collect the particles that move and record the number;
[0069] F. Calculate the qualified rate of magnetizable iron and the magnetizable rate, where:
[0070] Qualified rate of magnetizable iron = (total number of particles - number of unqualified particles) ÷ total number of particles × 100%;
[0071] Magnetizable rate = number of unqualified particles / total number of particles × 100%.
[0072] Example 1
[0073] This embodiment adopts the following steps to prepare low magnetic oil-soluble aniline black:
[0074] (1) adding aniline and recovered aniline into a preheating kettle, and under stirring, adding ferric chloride into the preheating kettle at a feeding rate of 12 g / min. After the addition of ferric chloride is completed, sealing the feed port of the preheating kettle, adjusting the steam valve for heating, and stopping heating after the temperature is raised to above 125° C., and conveying the preheated materials into a condensation kettle;
[0075] (2) After the material transportation is completed, the condensation kettle is heated to 170° C. by a thermal oil furnace, the temperature-raising valve of the thermal oil furnace is closed, and nitrobenzene is added to the condensation kettle at a feeding rate of 1.5 ml / min by a flow meter. During the addition of nitrobenzene, the temperature of the material in the condensation kettle is controlled to be 170-185° C.; after the addition of nitrobenzene is completed, the temperature is kept for 1 hour, and then the temperature is raised to 190° C. to obtain a condensate; wherein the molar ratio of aniline, nitrobenzene and ferric chloride is 2.37:1:0.23;
[0076] (3) adding hydrochloric acid and hot water to the acidification kettle, turning on the steam heating to 70° C., and transferring the condensate obtained in step (2) to the acidification kettle under stirring while maintaining the temperature at 70° C.; pumping the acidified material to the filter for water washing until the acid content of the obtained washing wastewater is less than or equal to 0.5%, thereby obtaining a filter cake;
[0077] (4) taking 2.1 g of a nitric acid solution having a mass concentration of 65%, adding it to 90 g of water for dilution; taking 60 g of the filter cake obtained in step (3) (the mass of nitric acid is equivalent to 2.3% of the mass of the filter cake), adding it to the diluted nitric acid solution for pulping, heating it to 80° C., and keeping it warm for 4 hours for oxidation treatment;
[0078] (5) mixing liquid caustic soda with hot water at a temperature of 90° C., adding the slurry material after oxidation treatment obtained in step (4), and then continuing to add liquid caustic soda to adjust the pH to 10.5, then raising the temperature to 95° C. and keeping the temperature for 4 hours to perform saponification treatment;
[0079] (6) The saponified material is washed with water and then dried by flash evaporation. The flash evaporation outlet temperature is controlled to be about 65° C. The water content of the obtained aniline black product is 1.5%.
[0080] In this embodiment, the qualified rate of magnetizable iron in the obtained aniline black product is 100%, and the magnetizability is 0%.
[0081] Example 2
[0082] This embodiment adopts the following steps to prepare low magnetic oil-soluble aniline black:
[0083] (1) adding aniline and recovered aniline into a preheating kettle, and under stirring, adding ferric chloride into the preheating kettle at a feeding rate of 12 g / min. After the addition of ferric chloride is completed, sealing the feed port of the preheating kettle, adjusting the steam valve for heating, and stopping heating after the temperature is raised to above 125° C., and conveying the preheated materials into a condensation kettle;
[0084] (2) After the material transportation is completed, the condensation kettle is heated to 173° C. by a thermal oil furnace, the temperature-raising valve of the thermal oil furnace is closed, and nitrobenzene is added to the condensation kettle at a feeding rate of 1.4 ml / min by a flow meter. During the addition of nitrobenzene, the temperature of the material in the condensation kettle is controlled to be 170-185° C.; after the addition of nitrobenzene is completed, the temperature is kept for 1 hour, and then the temperature is raised to 192° C. to obtain a condensate; wherein the molar ratio of aniline, nitrobenzene and ferric chloride is 2.37:1:0.23;
[0085] (3) adding hydrochloric acid and hot water to the acidification kettle, turning on the steam heating to 75° C., and transferring the condensate obtained in step (2) to the acidification kettle under stirring while maintaining the temperature at 75° C.; pumping the acidified material to the filter for water washing until the acid content of the obtained washing wastewater is less than or equal to 0.5%, thereby obtaining a filter cake;
[0086] (4) taking 2.1 g of a nitric acid solution having a mass concentration of 65%, adding it to 90 g of water for dilution; taking 60 g of the filter cake obtained in step (3) (the mass of nitric acid is equivalent to 2.3% of the mass of the filter cake), adding it to the diluted nitric acid solution for pulping, heating it to 80° C., and keeping it warm for 4 hours for oxidation treatment;
[0087] (5) mixing liquid caustic soda with hot water at a temperature of 90° C., adding the slurry material after oxidation treatment obtained in step (4), and then continuing to add liquid caustic soda to adjust the pH to 10.8, then raising the temperature to 96° C. and keeping the temperature for 4 hours to perform saponification treatment;
[0088] (6) The saponified material is washed with water and then dried by flash evaporation. The flash evaporation outlet temperature is controlled to be 65° C. The water content of the obtained aniline black product is 2.0%.
[0089] In this embodiment, the qualified rate of magnetizable iron of the obtained aniline black product is 99%, and the magnetizability is 1%.
[0090] Example 3
[0091] This embodiment adopts the following steps to prepare low magnetic oil-soluble aniline black:
[0092] (1) adding aniline and recovered aniline into a preheating kettle, and under stirring, adding ferric chloride into the preheating kettle at a feeding rate of 12 g / min. After the addition of ferric chloride is completed, sealing the feed port of the preheating kettle, adjusting the steam valve for heating, and stopping heating after the temperature is raised to above 125° C., and conveying the preheated materials into a condensation kettle;
[0093] (2) After the material transportation is completed, the condensation kettle is heated to 170° C. by a thermal oil furnace, the temperature-raising valve of the thermal oil furnace is closed, and nitrobenzene is added to the condensation kettle at a feeding rate of 1.4 ml / min by a flow meter. During the addition of nitrobenzene, the temperature of the material in the condensation kettle is controlled to be 170-185° C.; after the addition of nitrobenzene is completed, the temperature is kept for 1 hour, and then the temperature is raised to 190° C. to obtain a condensate; wherein the molar ratio of aniline, nitrobenzene and ferric chloride is 2.37:1:0.23;
[0094] (3) adding hydrochloric acid and hot water to the acidification kettle, turning on the steam heating to 70° C., and transferring the condensate obtained in step (2) to the acidification kettle under stirring while maintaining the temperature at 70° C.; pumping the acidified material to the filter for water washing until the acid content of the obtained washing wastewater is less than or equal to 0.5%, thereby obtaining a filter cake;
[0095] (4) taking 1.4 g of a nitric acid solution having a mass concentration of 65%, adding it to 90 g of water for dilution; taking 60 g of the filter cake obtained in step (3) (the mass of nitric acid is equivalent to 1.5% of the mass of the filter cake), adding it to the diluted nitric acid solution for pulping, heating it to 80° C., and keeping it warm for 4 hours for oxidation treatment;
[0096] (5) mixing liquid caustic soda with hot water at a temperature of 90° C., adding the slurry material after oxidation treatment obtained in step (4), and then continuing to add liquid caustic soda to adjust the pH to 10.5, then raising the temperature to 95° C. and keeping the temperature for 4 hours to perform saponification treatment;
[0097] (6) The saponified material is washed with water and then dried by flash evaporation. The flash evaporation outlet temperature is controlled to be 65° C. The water content of the obtained aniline black product is 1.5%.
[0098] In this embodiment, the qualified rate of magnetizable iron of the obtained aniline black product is 99%, and the magnetizability is 1%.
[0099] Example 4
[0100] This embodiment adopts the following steps to prepare low magnetic oil-soluble aniline black:
[0101] (1) adding aniline and recovered aniline into a preheating kettle, and under stirring, adding ferric chloride into the preheating kettle at a feeding rate of 12 g / min. After the addition of ferric chloride is completed, sealing the feed port of the preheating kettle, adjusting the steam valve for heating, and stopping heating after the temperature is raised to above 125° C., and conveying the preheated materials into a condensation kettle;
[0102] (2) After the material transportation is completed, the condensation kettle is heated to 172° C. by a thermal oil furnace, the temperature-raising valve of the thermal oil furnace is closed, and nitrobenzene is added to the condensation kettle at a feeding rate of 1.5 ml / min by a flow meter. During the addition of nitrobenzene, the temperature of the material in the condensation kettle is controlled to be 170-185° C.; after the addition of nitrobenzene is completed, the temperature is kept for 1 hour, and then the temperature is raised to 192° C. to obtain a condensate; wherein the molar ratio of aniline, nitrobenzene and ferric chloride is 2.37:1:0.23;
[0103] (3) adding hydrochloric acid and hot water to the acidification kettle, turning on the steam heating to 75° C., and transferring the condensate obtained in step (2) to the acidification kettle under stirring while maintaining the temperature at 75° C.; pumping the acidified material to the filter for water washing until the acid content of the obtained washing wastewater is less than or equal to 0.5%, thereby obtaining a filter cake;
[0104] (4) taking 1.4 g of a nitric acid solution having a mass concentration of 65%, adding it to 90 g of water for dilution; taking 60 g of the filter cake obtained in step (3) (the mass of nitric acid is equivalent to 1.5% of the mass of the filter cake), adding it to the diluted nitric acid solution for pulping, heating it to 80° C., and keeping it warm for 4 hours for oxidation treatment;
[0105] (5) mixing liquid caustic soda with hot water at a temperature of 90° C., adding the slurry material after oxidation treatment obtained in step (4), and then continuing to add liquid caustic soda to adjust the pH to 10.8, then raising the temperature to 96° C. and keeping the temperature for 4 hours to perform saponification treatment;
[0106] (6) The saponified material was washed with water and then dried by flash evaporation. The flash outlet temperature was controlled to be 65° C. The water content of the obtained aniline black product was 1.8%.
[0107] In this embodiment, the qualified rate of magnetizable iron of the obtained aniline black product is 98%, and the magnetizability is 2%.
[0108] Example 5
[0109] This embodiment adopts the following steps to prepare low magnetic oil-soluble aniline black:
[0110] (1) adding aniline and recovered aniline into a preheating kettle, and under stirring, adding ferric chloride into the preheating kettle at a feeding rate of 12 g / min. After the addition of ferric chloride is completed, sealing the feed port of the preheating kettle, adjusting the steam valve for heating, and stopping heating after the temperature is raised to above 125° C., and conveying the preheated materials into a condensation kettle;
[0111] (2) After the material transportation is completed, the condensation kettle is heated to 175° C. by a thermal oil furnace, the temperature-raising valve of the thermal oil furnace is closed, and nitrobenzene is added to the condensation kettle at a feeding rate of 1.6 ml / min by a flow meter. During the addition of nitrobenzene, the temperature of the material in the condensation kettle is controlled to be 170-185° C.; after the addition of nitrobenzene is completed, the temperature is kept for 1 hour, and then the temperature is raised to 192° C. to obtain a condensate; wherein the molar ratio of aniline, nitrobenzene and ferric chloride is 2.37:1:0.23;
[0112] (3) adding hydrochloric acid and hot water to the acidification kettle, turning on the steam heating to 75° C., and transferring the condensate obtained in step (2) to the acidification kettle under stirring while maintaining the temperature at 75° C.; pumping the acidified material to the filter for water washing until the acid content of the obtained washing wastewater is less than or equal to 0.5%, thereby obtaining a filter cake;
[0113] (4) taking 1.4 g of a nitric acid solution having a mass concentration of 65%, adding it to 90 g of water for dilution; taking 60 g of the filter cake obtained in step (3) (the mass of nitric acid is equivalent to 1.5% of the mass of the filter cake), adding it to the diluted nitric acid solution for pulping, heating it to 80° C., and keeping it warm for 4 hours for oxidation treatment;
[0114] (5) mixing liquid caustic soda with hot water at a temperature of 90° C., adding the slurry material after oxidation treatment obtained in step (4), and then continuing to add liquid caustic soda to adjust the pH to 11.0, then raising the temperature to 96° C. and keeping the temperature for 4 hours to perform saponification treatment;
[0115] (6) The saponified material was washed with water and then dried by flash evaporation. The flash outlet temperature was controlled to be 65° C. The water content of the obtained aniline black product was 1.9%.
[0116] In this embodiment, the qualified rate of magnetizable iron of the obtained aniline black product is 99%, and the magnetizability is 1%.
[0117] Comparative Example 1
[0118] This comparative example adopts the following steps to prepare the aniline black product:
[0119] (1) adding aniline and recovered aniline into a preheating kettle, and under stirring, adding ferric chloride into the preheating kettle at a feeding rate of 12 g / min. After the addition of ferric chloride is completed, sealing the feed port of the preheating kettle, adjusting the steam valve for heating, and stopping heating after the temperature is raised to above 125° C., and conveying the preheated materials into a condensation kettle;
[0120] (2) After the material transportation is completed, the condensation kettle is heated to 170° C. by a thermal oil furnace, the temperature-raising valve of the thermal oil furnace is closed, and nitrobenzene is added to the condensation kettle at a feeding rate of 1.5 ml / min by a flow meter. During the addition of nitrobenzene, the temperature of the material in the condensation kettle is controlled to be 170-185° C.; after the addition of nitrobenzene is completed, the temperature is kept for 1 hour, and then the temperature is raised to 190° C. to obtain a condensate; wherein the molar ratio of aniline, nitrobenzene and ferric chloride is 2.37:1:0.23;
[0121] (3) adding hydrochloric acid and hot water to the acidification kettle, turning on the steam heating to 70° C., and transferring the condensate obtained in step (2) to the acidification kettle under stirring while maintaining the temperature at 70° C.; pumping the acidified material to the filter for water washing until the acid content of the obtained washing wastewater is less than or equal to 0.5%, thereby obtaining a filter cake;
[0122] (4) adding liquid alkali and hot water at a temperature of 90° C. into a saponification kettle, adding the filter cake obtained in step (3) into the saponification kettle through a screw conveyor under stirring conditions, and then continuing to add liquid alkali to adjust the pH to 10.5, then raising the temperature to 95° C. and keeping the temperature for 4 hours;
[0123] (5) The material in the saponification kettle is transported to the filter for water washing, and the washed material is transported to the flash drying unit by a screw conveyor; the wet material enters the feed tank in the flash drying unit for storage, and is transported to the flash main unit by a screw conveyor in the feed tank for drying, and the flash outlet temperature is controlled to be 65° C. The water content of the obtained aniline black product is 1.8%.
[0124] Comparative Example 2
[0125] The difference between this comparative example and the above-mentioned Example 1 is that hydrogen peroxide is used as the oxidant instead of nitric acid.
[0126] Specifically, in step (4), 7.5 ml of 27.5% hydrogen peroxide was taken and diluted in 81.75 g of water, and then 60 g of the filter cake obtained in step (3) was added to the diluted hydrogen peroxide and slurried, and kept at 80° C. for 2 hours to perform oxidation treatment. Steps (1) to (3) and steps (5) and (6) are the same as those in the above-mentioned Example 1.
[0127] Comparative Example 3
[0128] The difference between this comparative example and the above-mentioned Example 1 is that nitric acid is added between the acidification step and the water washing step to oxidize the material. Specifically, the aniline black product is prepared by the following steps:
[0129] (1) adding aniline and recovered aniline into a preheating kettle, and under stirring, adding ferric chloride into the preheating kettle at a feeding rate of 12 g / min. After the addition of ferric chloride is completed, sealing the feed port of the preheating kettle, adjusting the steam valve for heating, and stopping heating after the temperature is raised to above 125° C., and conveying the preheated materials into a condensation kettle;
[0130] (2) After the material transportation is completed, the condensation kettle is heated to 170° C. by a thermal oil furnace, the temperature-raising valve of the thermal oil furnace is closed, and nitrobenzene is added to the condensation kettle at a feeding rate of 1.5 ml / min by a flow meter. During the addition of nitrobenzene, the temperature of the material in the condensation kettle is controlled to be 170-185° C.; after the addition of nitrobenzene is completed, the temperature is kept for 1 hour, and then the temperature is raised to 190° C. to obtain a condensate; wherein the molar ratio of aniline, nitrobenzene and ferric chloride is 2.37:1:0.23;
[0131] (3) adding hydrochloric acid and hot water into the acidification kettle, turning on the steam heating to 70° C., and transferring the condensate obtained in step (2) into the acidification kettle for acidification treatment under stirring while maintaining the temperature at 70° C.;
[0132] (4) taking 120 g of the slurry after the acidification treatment (equivalent to 60 g of the filter cake), adding 2.1 g of a nitric acid solution with a mass concentration of 65%, raising the temperature to 80° C., and keeping the temperature for 4 hours for oxidation treatment;
[0133] (5) The material after oxidation treatment is pumped to a filter for water washing until the acid content is less than or equal to 0.5%, thereby obtaining a filter cake;
[0134] (6) mixing liquid caustic soda with hot water at a temperature of 90° C., adding the slurry material after oxidation treatment obtained in step (4), and then continuing to add liquid caustic soda to adjust the pH to 10.5, then raising the temperature to 95° C. and keeping the temperature for 4 hours to perform saponification treatment;
[0135] (7) The saponified material was washed with water and then dried by flash evaporation. The flash outlet temperature was controlled at 65° C. The water content of the obtained aniline black product was 2.2%.
[0136] Comparative Example 4
[0137] The difference between this comparative example and the above-mentioned Example 1 is that nitric acid is added between the saponification step and the water washing step to oxidize the material. Specifically, the aniline black product is prepared by the following steps:
[0138] (1) adding aniline and recovered aniline into a preheating kettle, and under stirring, adding ferric chloride into the preheating kettle at a feeding rate of 12 g / min. After the addition of ferric chloride is completed, sealing the feed port of the preheating kettle, adjusting the steam valve for heating, and stopping heating after the temperature is raised to above 125° C., and conveying the preheated materials into a condensation kettle;
[0139] (2) After the material transportation is completed, the condensation kettle is heated to 170° C. by a thermal oil furnace, the temperature-raising valve of the thermal oil furnace is closed, and nitrobenzene is added to the condensation kettle at a feeding rate of 1.5 ml / min by a flow meter. During the addition of nitrobenzene, the temperature of the material in the condensation kettle is controlled to be 170-185° C.; after the addition of nitrobenzene is completed, the temperature is kept for 1 hour, and then the temperature is raised to 190° C. to obtain a condensate; wherein the molar ratio of aniline, nitrobenzene and ferric chloride is 2.37:1:0.23;
[0140] (3) adding hydrochloric acid and hot water to the acidification kettle, turning on the steam heating to 70° C., and transferring the condensate obtained in step (2) to the acidification kettle under stirring while maintaining the temperature at 70° C.; pumping the acidified material to the filter for water washing until the acid content of the obtained washing wastewater is less than or equal to 0.5%, thereby obtaining a filter cake;
[0141] (4) mixing liquid caustic soda with hot water at a temperature of 90° C., adding 60 g of the filter cake obtained in step (3) to make a pulp, then continuing to add liquid caustic soda to adjust the pH to 10.5, then raising the temperature to 95° C. and keeping the temperature for 4 hours for saponification treatment;
[0142] (5) adding 2.1 g of 65% nitric acid solution to the saponified material, heating to 80° C., and keeping the temperature for 4 hours for oxidation treatment;
[0143] (6) The material after oxidation treatment is pumped to a filter for water washing, and then dried by flash evaporation. The flash evaporation outlet temperature is controlled at 65° C. The water content of the obtained aniline black product is 1.8%.
[0144] Test Example 1
[0145] In this test example, the aniline black products prepared in the above-mentioned embodiments 1-5 and comparative examples 1-4 were tested, and the specific test results are shown in the following Table 1.
[0146] Table 1
[0147]
[0148]
[0149] It can be seen from the above test data that compared with Comparative Example 1, by adding the step of adding nitric acid for oxidation treatment during the preparation process, the magnetic susceptibility of the prepared aniline black product is significantly reduced, indicating that the addition of nitric acid effectively removes Fe in the filter cake. 2+ Oxidized to Fe3 + , realizing the production of low-magnetic oil-soluble aniline black.
[0150] By comparing the test results of Example 1 with those of Comparative Examples 1 and 2, it can be seen that, although the use of hydrogen peroxide as an oxidant can reduce the magnetizability of the nigrosine product to a certain extent, the reduction is limited, and the obtained nigrosine product still has a relatively high magnetizability. This may be because when hydrogen peroxide is used as an oxidant, although it has a certain oxidizing effect, the reaction is too violent, which leads to a poor oxidation effect. It can be seen that in the present invention, nitric acid is selected as an oxidant to reduce the Fe in the filter cake. 2+ Oxidized to Fe3 +, which has a better effect in reducing the magnetizable rate of aniline black products.
[0151] By comparing the test results of Example 1 with those of Comparative Examples 3 and 4, it can be seen that when the amount of nitric acid used is the same, the magnetic susceptibility of the aniline black product obtained in Comparative Example 3 is higher than that in Example 1. This is because when the water washing step is not performed, the Fe 2+ The content is too high, and a larger amount of nitric acid is needed to fully oxidize it. Although the aniline black product prepared in Comparative Example 4 is comparable to Example 1 in terms of the index of magnetizability, the pH value of the product is too low, which leads to the problem of being unqualified in the pH value detection. It can be seen that the oxidation treatment of the material after acidification and water washing in the present invention can reduce the amount of nitric acid as much as possible, and while obtaining a aniline black product with low magnetizability, its pH value can also be controlled within an appropriate range.
[0152] Test Example 2
[0153] This test example is used to investigate the effect of reaction temperature on the magnetizable properties of the obtained nigrosine product during the oxidation treatment process. Specifically, the preparation method is the same as that in Example 1, except that the target temperature of the heating in step (4) is changed to prepare the nigrosine product, and its properties are tested. The results are shown in Table 2 below.
[0154] Table 2
[0155]
[0156]
[0157] It can be seen from the above test data that when the target temperature of the heating in step (4) is greater than or equal to 50°C, the magnetizable rate of the obtained aniline black product reaches a level not higher than 4%, and as the target temperature increases, the magnetizable rate first gradually decreases. After the target temperature reaches 100°C and continues to rise, the magnetizable rate increases slightly and stabilizes at 1%.
[0158] In the present invention, the target temperature of heating in step (4) is preferably controlled at 70-100°C, so that the magnetizable rate of the obtained aniline black product is controlled to be no higher than 1%. At the same time, the temperature of the saponification treatment in the subsequent step (5) is 95-98°C, which avoids the problem that the temperature of the material after oxidation treatment is too high and needs to be cooled for a long time. Further preferably, the target temperature of heating in step (4) is controlled at 80-90°C, so that a aniline black product with a magnetizable rate of 0% can be obtained.
[0159] Test Example 3
[0160] This test example is used to investigate the effect of the amount of nitric acid added on the magnetizable properties of the obtained nigrosine product during the oxidation treatment process. Specifically, the preparation method is the same as that in Example 1, except that the amount of nitric acid solution added in step (4) is changed to prepare the nigrosine product, and its properties are tested. The results are shown in Table 3 below.
[0161] Table 3
[0162] Amount of nitric acid solution added (g) Nitric acid percentage of filter cake mass (%) Magnetizable rate (%) 0.7 0.8 12 0.9 1.0 7 1.4 1.5 1 1.8 2.0 0 2.1 2.3 0 2.8 3.0 0 3.7 4.0 0
[0163] It can be seen from the above test data that with the increase in the amount of nitric acid solution added, the magnetizable rate of the obtained nigrosine product gradually decreases and can eventually stabilize at 0%. However, with the increase in the amount of nitric acid solution added, in order to control the pH value of the nigrosine product, the amount of liquid alkali used in the subsequent saponification treatment will also increase accordingly. Therefore, in the present invention, the amount of nitric acid is preferably controlled to 1.0% to 3.0% of the mass of the filter cake, and a nigrosine product with a magnetizable rate of not more than 7% can be obtained. More preferably, the amount of nitric acid is controlled to 1.5% to 2.3% of the mass of the filter cake, and a nigrosine product with a magnetizable rate of not more than 1% can be obtained, while minimizing the amount of liquid alkali used in the subsequent saponification treatment.
[0164] The above is only a preferred embodiment of the present invention, and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment, it is not used to limit the present invention. Any technician familiar with this patent can make some changes or modify the technical contents suggested above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the solution of the present invention.
Claims
1. A method for preparing low-magnetic oil-soluble aniline black, characterized in that: The following steps are involved: (1) mixing aniline raw material and ferric chloride, heating up and preheating; (2) adding nitrobenzene to the preheated material to carry out a condensation reaction to obtain a condensate; (3) acidifying and washing the condensate in sequence; (4) mixing the washed material with a nitric acid solution and performing an oxidation treatment; (5) mixing the oxidized material with liquid alkali and performing saponification treatment; (6) The saponified material is washed with water and dried in sequence to obtain a nigrosine product.
2. The method for preparing low-magnetic oil-soluble aniline black according to claim 1, characterized in that: In step (4), after the washed material is mixed with the nitric acid solution, the mixture is heated to 70-100° C. and kept warm for 2-4 hours; Preferably, the mixture is heated to 80-90° C. and kept warm for 2-4 hours; More preferably, the mixture is heated to 80°C and maintained at that temperature for 4 hours.
3. The method for preparing low-magnetic oil-soluble aniline black according to claim 1 or 2, characterized in that: In step (3), the acidified material is washed with water using a filter, and the washed material obtained is a filter cake; In step (4), the mass of nitric acid in the nitric acid solution is 1.0% to 3.0% of the mass of the filter cake in step (3), preferably 1.5% to 2.3%; Preferably, in step (3), the material is washed with water until the acid content of the obtained washing wastewater is less than or equal to 0.5%.
4. The method for preparing low-magnetic oil-soluble aniline black according to claim 3, characterized in that: In step (4), a nitric acid solution with a mass concentration of 65% to 68% is added to water for dilution, and the filter cake obtained in step (3) is added to the diluted nitric acid solution, and the temperature is increased for oxidation treatment; Preferably, the mass of water used to dilute the nitric acid solution is 1 to 3 times the mass of the filter cake, preferably 1.5 times.
5. The method for preparing low-magnetic oil-soluble aniline black according to any one of claims 1 to 4, characterized in that: In step (5), liquid alkali and hot water at a temperature of 90 to 95° C. are added to the saponification kettle, and then the oxidized material obtained in step (4) is added to the saponification kettle, and then liquid alkali is continued to be added to adjust the pH to 10 to 12, and then the temperature is raised to 95 to 98° C. and kept warm for 4 to 6 hours to complete the saponification treatment.
6. The method for preparing low-magnetic oil-soluble aniline black according to any one of claims 1 to 5, characterized in that: In step (1), the aniline raw material comprises aniline and recovered aniline; wherein the recovered aniline comprises aniline with a mass fraction greater than 95% and the remainder being water; Preferably, the mass ratio of the aniline to the recovered aniline is 1:0.6-0.
65.
7. The method for preparing low-magnetic oil-soluble aniline black according to claim 6, characterized in that: In step (1), aniline and recovered aniline are added to a preheating kettle, and ferric chloride is added to the preheating kettle under stirring. After the addition of ferric chloride is completed, the preheating kettle is sealed, and the temperature is raised to above 100 to 130° C. and then stopped, and the preheated materials are transported to a condensation kettle; Preferably, ferric chloride is added into the preheating kettle at a rate of 10-15 g / min.
8. The method for preparing low-magnetic oil-soluble aniline black according to any one of claims 1 to 7, characterized in that: Step (2) specifically includes: The preheated material is transported to the condensation kettle and heated to 170-175°C; Add nitrobenzene to the condensation kettle. During the addition of nitrobenzene, control the temperature of the material in the condensation kettle to be 170-185°C; After the addition of nitrobenzene is completed, the temperature is kept at 1 to 2 hours, and then the temperature is raised to 190 to 200°C to obtain a condensate; Preferably, nitrobenzene is added to the condensation reactor at a rate of 1.4 to 1.6 ml / min; Preferably, the molar ratio of aniline, nitrobenzene and ferric chloride in the aniline raw material is 2.1-3.0:1:0.23-0.28; More preferably, the molar ratio of aniline, nitrobenzene and ferric chloride is 2.37:1:0.
23.
9. The method for preparing low-magnetic oil-soluble aniline black according to any one of claims 1 to 8, characterized in that: In step (3), hydrochloric acid and water are added to an acidification kettle and heated to 70-80° C., and then the condensate obtained in step (2) is transferred to the acidification kettle under stirring conditions for acidification treatment.
10. The method for preparing low-magnetic oil-soluble aniline black according to any one of claims 1 to 9, characterized in that: In step (6), a flash dryer is used to dry the washed material, and the flash outlet temperature is controlled to be 64-66° C.; the water content of the aniline black product obtained after drying is 1.0%-3.0%.